Contribution of indigenous foods towards nutrient intakes and nutritional status of women in the Santhal tribal community of Jharkhand, India. Issue 12 (16th March 2016) - Ghosh-Jerath, Suparna; Singh, Archna; Magsumbol, Melina S; Lyngdoh, Tanica; Kamboj, Preeti; Goldberg, Gail
Abstract: Objective: The indigenous food environment, dietary intake and nutritional status of women in the Santhal tribal community of Jharkhand were assessed. Contribution of indigenous foods to nutritional status and nutrient intakes was explored. Design: Exploratory cross-sectional study with a longitudinal dietary intake assessment component. Household and dietary surveys were conducted to elicit information on socio-economic and demographic profile and food consumption patterns at household level. A 24 h dietary recall for two consecutive days (repeat surveys in two more seasons) and anthropometric assessments were carried out on one woman per household. Setting: Households ( n 151) with at least one woman of reproductive age in four villages of Godda district of Jharkhand, India. Subjects: Women aged 15–49 years. Results: Almost all households owned agricultural land and grew fruits and vegetables in backyards for household consumption. A wide variety of indigenous foods were reported but dietary recalls revealed low intake. Women consumed adequate energy and protein but micronutrient intake was inadequate (less than 66 % of recommended) in the majority (more than 50 %) for Ca, Fe, vitamin B2, folate and vitamin B12 . Women consuming indigenous foods in the past 2 d had significantly higher intakes of Ca ( P= 0·008) and Fe ( P= 0·010) than those who did not. Varying degrees of underweight were observed in 50 % of women with no significant association between underweight and consumption of indigenous foods. Conclusions: Promotion of preferential cultivation of nutrient-dense indigenous food sources and effective nutrition education on their importance may facilitate better micronutrient intakes among women in Santhal community of Jharkhand.